Pengaruh Pengetahuan Keuangan Syariah Terhadap Penggunaan Pinjaman Online Pada Mahasiswa Universitas Alwashliyah Medan - Yurmaini Yurmaini; Erliyanti Erliyanti; Khairil Anshari; Rahmadiah Wahyuni Naibaho; Rahanum Rahanum (Jayapangus Press, 2026)
The current development of financial technology, particularly online lending services (pinjol), has become a phenomenon closely related to everyday life, including that of students. Ease of access, fast processing, and minimal requirements make these services attractive, but behind them lurk significant potential risks such as debt traps, high interest rates, and involvement in illegal lending. The urgency of this research lies in the increasing number of online loan users among students, who often do so without an adequate understanding of Islamic finance. The purpose of this study is to determine the extent to which Islamic financial knowledge influences students' decision-making in using online lending services and to provide a basis for universities and related parties in formulating educational strategies and Islamic financial protection policies. The research method used is a quantitative survey approach. The study population was students at Alwashliyah University Medan, while the sample was 176 students who had used online loans. The sampling technique used was purposive sampling. The results of the study indicate that the sample size used is still relatively small, resulting in a coefficient of determination (R2) of 0.60, or only 6%, of Islamic financial knowledge contributing to online loans for Alwashliyah University students. Furthermore, the higher the level of Islamic financial knowledge, the lower the tendency of students to use online loans. Furthermore, the importance of strengthening Islamic financial literacy in an applied manner and the need for further research by considering external factors that also influence online loan usage behavior among students.